Facilitators and Barriers to the Adoption of an Electronic Medical Record System by Intensive Care Nurses. - Osajiuba,SA; Jedwab,R; Calvo,R; Dobroff,N; Glozier,N; Hutchinson,A; Leiter,M; Nankervis,K; Rawson,H; Redley,B; Manias,E (2021)
Introducing new technology, such as an electronic medical record (EMR) into an Intensive Care Unit (ICU), can contribute to nurses' stress and negative consequences for patient safety. The aim of this study was to explore ICU nurses' perceptions of factors expected to influence their adoption of an EMR in their workplace. The objectives were to: 1) measure psychological factors expected to influence ICU nurses' adoption of EMR, and 2) explore perceptions of facilitators and barriers to the implementation of an EMR in their workplace. Using an explanatory sequential mixed method approach, data were collected using surveys and focus groups. ICU nurses reported high scores for motivation, work engagement and wellbeing. Focus group analyses revealed two themes: Hope the EMR will bring a new world and Fear of unintended consequences. Recommendations relate to strategies for education and training, environmental restructuring and enablement. Overall, ICU nurses were optimistic about EMR implementation.